Porosity verification of gas-bearing F3 reservoir, Al Wafa Oil Field, Ghadames Basin, Libya - Ben Ghawar, Bahia Muftah; Ibrahim , Ibrahim; El-Muqassbi, Qusai; Al-Ghellali, Salem (Geological Agency, 2026)
Porosity is a critical physical property of reservoir rocks. It has a significant contribution for development strategic plans, and 3D building models reservoir rocks of oil fields. However, well logs and core samples are two sources of direct and indirect rock porosity data. Hence, porosity logs; neutron porosity (Øn), bulk density (ρb), and interval travel time (ΔT) designate a fluctuation of the porosity values within gas-bearing rocks. Accordingly, this work is concerned with the investigation of an impacting of the porosity logs of the three porosity logs on the water saturation (Sw) estimation, as a petrophysical assessment of the gas bearing F3 Sandstone reservoir (Aouinet Uennin Formation, Devonian). Thus, well log data has been taken and processed from eight wells, these wells produce about 124 feet, an average thickness of the F3 Sandstone reservoir of the Al Wafa Gas and Oil Field, Ghadames Basin. Therefore, this Devonian clean sandstone and gas-bearing reservoir has a volume shale of less than 25%, which may be considered a potassium feldspar sandstone rock type. In addition, total porosity (Ønd), neutron porosity (Øn), and sonic porosity (Øsnc) illustrate reduction values due to the gas effect or implementation, which causes uncertainty estimation of the water saturation. Whereas the density porosity (Ød) yields a moderation values that are highly in agreement with the core porosity. This later result reveals less uncertainty of the petrophysical assessment in the F3 Sandstone gas-bearing reservoir.